SENSORY QUALITY STATUS OF DRIED SALTED SQUID (Loligo sp) MARKETED IN PASAR PAGI ARENGKA MARKET OF PEKANBARU - Rika Sepia Alvianti; Bustari Hasan; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT             This study aims to evaluate the sensory quality status of dried salted squid marketed in Pasar Pagi Arengka Market of Pekanbaru. Dried salted squids were selected based on their region of origin, namely Sibolga and Tanjung Pinang and their storage age of 1 week and 2 weeks, then samples were taken from the market. Samples were taken randomly from three traders and analyzed for sensory quality (odor, taste, texture, appearance). The sensory quality results of dried salted squid varied between product origin and storage age. Dried salted squid from Tanjung Pinang and Sibolga had sensory quality values of 7.77 and 7.48. The sensory quality of dried salted squid based on 1 week and 2 weeks shelf life has a value of 7.89 and 7.36. Based on this assessment, dried salted squid still meets the Indonesian National Standard (minimum 7).Keyword : Dried salted squid, Market, Sensory, Loligo sp